Transparência no Poder Judiciário: um estudo nos Tribunais de Justiça dos estados brasileiros - Cruz, Gustavo Juliano Leitao da (2019)
The transparency of governmental actions is foundational for the strengthening of the relations between State and society. Studies carried out in the legislative, executive and judicial branches of government in the three levels of the Brazilian Federation administration (Federal, State, and Local) indicate an insufficient level of transparency. This dearth of transparency reveals formalistic praxis that, according to theory, is the existing disagreement between legal stipulations and the actions executed by government and society. The formalism evidenced in these studies associated to the characteristics of the Judiciary, that stand in opposition to the democratic principle of the full disclosure of information (bureaucratic representation, constitutional competency to protect the individual guarantees and rights, and cultural traits of authoritarianism), instigated the analysis of the how State Courts of Justice comply the demands of active and passive transparency foreseen legislation. The Active transparency study consisted in the verification, accessing the Courts’ web pages, of the established observation guidelines based on the proactive dissemination standards of information established by the National Justice Counsel (Conselho Nacional de Justiça – CNJ). The passive transparency study, founded in the 2011 Law number 12.527 (Information Access Law), was based on the analysis of the behavior of the Courts with regard to the fulfillment of requests for information fowarded. The research results demonstrate that the State Judiciary does not adequately comply with the transparency requirements foreseen in the legislation and is barely committed to democratic issues.